INTER-CONFESSIONAL RELATIONS AS A SPECIAL TYPE OF SOCIAL RELATIONS: RUSSIA’S POLY-CULTURAL MILIEU - BUTTAEVA, Asiyat; KAKHAEV, Akhmed (CENTRAL ASIA AND THE CAUCASUS, 2020)
In Russia, which is a poly-cultural state, the problem of international and inter- confessional relations is invariably on top of the agenda. This is especially apparent in the south of Russia, where Orthodoxy and Islam have been coexisting for a long time and where the acculturation and assimilation processes are highly rigorous and contradictory. Disintegration of the atheist ideology imparted greater signi the religious and cultural speci moved all ideological barriers. This had radically transformed the social context and the world-views of the local population and intensi gagement of confessions, primarily, Ortho- doxy and Islam.History has taught us that the coexistence of ethno confessional communities on the Russian soil has been fairly complicated and highly ambiguous. On the one hand, there was latent or even open opposition; on the other, cooperation and interpenetration.We are convinced that many aspects of this process were conditioned by the complex history and by the struggle between different political and religious forces and private interests that emerged as a spiritual component of life of different ethnicities. Today, the relations between members of different ethnic and confessional communities and their institutions are shaped by globalization and the ambiguous ethnoconfessional policy of the Russian state.The inter-confessional relations in the poly-cultural contemporary Russia should be analyzed with particular care because the two great cultures—Orthodox and Islamic—are not merely different. Their world- views are burdened by ideological contradictions, the settlement of which may lead to conflicts and clashes. On the other hand, dissimilar world views of religious cultures are not necessarily a source of confrontations. The latter are ignited by certain accompanying socio-cultural conditions and other forms of inter-confessional contradictions. Today, the poly-cultural milieu is fraught with conflicts and contradictions of this type.The paper examines the essence of Russia’s contemporary context and its impact on inter-confessional relations. We are convinced that their nature and content determine, to a great extent, the consistent development of the poly-cultural milieu.The historical phenomena of religious macro-communities continue to actively manifest themselves in confrontations that are developing into “civilizational splits.” The authors are convinced that a constructive cultural dialog as one of the important factors of stability is largely a constructive, albeit not always obvious, dialog of confessions.The structure of Russian society is highly complex, which means that inter-confessional agreement based on tolerance and a dialog is a must.We have pointed out that consent and poly-cultural tolerance between confessions are two indispensable conditions for the peaceful coexistence of two or more religions. Their absence leads to confrontations and the domination of one confession over the others, even without social upheavals in the best-case scenario. More likely than not, the prevailing confession is protected by the state, which means a retreat from the concept of a secular state.